AIM1, a novel non-lens member of the βγ-crystallin superfamily, is associated with the control of tumorigenicity in human malignant melanoma - Ray, Michael E. (The National Academy of Sciences of the USA, 1997)
AIM1 is a novel gene whose expression is associated with the experimental reversal of tumorigenicity of human malignant melanoma. The predicted protein product of the major 4.1-kb transcript shows striking similarity to the βγ-crystallin superfamily. All known members of this superfamily contain two or four characteristic motifs arranged as one or two symmetrical domains. AIM1, in contrast, contains 12 βγ motifs, suggesting a 6-domain structure resembling a trimer of β- or γ-crystallin subunits. The structure of the AIM1 gene shows remarkable similarity to β-crystallin genes, with homologous introns delineating equivalent protein structural units. AIM1 is the first mammalian member of the βγ superfamily with a primarily non-lens role. Other parts of the predicted AIM1 protein sequence have weak similarity with filament or actin-binding proteins. AIM1 is a good candidate for the putative suppressor of malignant melanoma on chromosome 6, possibly exerting its effects through interactions with the cytoskeleton.